Synchronous Vibration Control of MSCSG Based on High-Precision Closed-Loop Synchronous Rotating Frame Transformation - Han, Wenjing; Cai, Yuanwen; Han, Wenting; Yu, Chunmiao; Ren, Yuan; Wang, Weijie; Yin, Zengyuan (IEEE transactions on power electronics, 2025)
Due to rotor mass imbalance, magnetic suspension control sensitive gyroscope (MSCSG) has synchronous vibration. In order to reduce the influence of the above unbalance vibration on the performance of MSCSG and the measurement accuracy of angular velocity, a method to suppress the imbalance vibration based on the high-precision closed-loop synchronous rotating frame transformation method is proposed. First, the unbalance vibration torque dynamics model of MSCSG with mass unbalance was established, and the influence of unbalance vibration on the measurement accuracy of attitude angular velocity was analyzed. Then, a high-precision closed loop synchronous rotating frame transformation (HCSRF) controller is designed. A high-precision closed loop detection method including PI controller and low pass filter is used to improve the detection accuracy of synchronous signal. A HCSRF controller is used to suppress synchronous disturbance current of two channels simultaneously. Finally, aiming at the dual-input and output and strong coupling characteristics of tilt channel, the equivalent conversion method is used to analyze the stability of system. Simulation and experimental results show that the proposed method can effectively suppress synchronous disturbance current and vibration torque, and reduce the influence of mass unbalance on the MSCSG performance and angular velocity measurement accuracy.